The Validity of the 2-Point Method for Assessing the Force-Velocity Relationship of the Knee Flexors and Knee Extensors: The Relevance of Distant Force-Velocity Testing - Sašek, Matic; Mirkov, Dragan M.; Hadžić, Vedran; Šarabon, Nejc (Frontiers in Physiology, 2022)
Over the past decade, force-velocity (F-v) profiling has emerged as a promising tool for assessing neuromuscular capacity to design individually tailored interventions in diverse populations. To date, a limited number of studies have addressed the optimization of the linear method for measuring F-v profiles of single-joint isokinetic movements. We aimed to simplify the measurement of knee extension (KE) and knee flexion (KF) isokinetic tasks by evaluating the most appropriate combination of two velocities (i.e. the 2-point method). Twenty-two healthy participants (11 males and 11 females) were included in the study. Isokinetic peak torque was measured at nine angular velocities (30-60-90-120-150-180-210-240-300°/s) and under isometric conditions (at 150° and 120° of KF for KE and KF, respectively). Maximal theoretical force (F0), maximal theoretical velocity (v0), the slope of the relationship (Sfv), and maximal theoretical power (Pmax) were derived from the linear F-V profiles of KE and KF and compared between the 9-point method and all possible combinations (36 in total) of the 2-point methods. The F-v profiles obtained from nine points were linear for KE (r= 0.98; 95% CI = 0.97-0.98) and KF (r = 0.96; 95% CI = 0.95-0.98), with F0 underestimating the isometric MVC force. Further analyzes revealed great to excellent validity (range: ICCs = 0.89 to 0.99; CV = 2.54 to 4.34%) and trivial systematic error (range: ES = -0.11 to 0.24) of the KE 2-point method F-v profile when F from distant velocities (30°/s, 60°/s, or 90°/s in combination with 210°/s, 240°/s, or 300°/s) was used. Similarly, great to excellent validity and a trivial systematic error of the KF 2-point method F-v profile were observed for the F0 and Pmax parameters (range: ICC = 0.90 to 0.96; CV = 2.94 to 6.38%; ES = -0.07 to 0.14) when using the previously described combinations of velocities. These results suggest that practitioners should consider using more distant velocities when performing a simplified 2-point isokinetic single-joint F-V profiling. In addition, F-v profile has a potential to distinguish between mechanical characteristics of knee extensors and flexors and could therefore serve as a potential descriptor in practice and further research.